Implementasi Sistem Informasi Puskesmas (SIP) di Puskesmas Baki Sukoharjo - Hakam, Fahmi (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2024)
The Primary Healthcare Information System is an arrangement that provides information to assist the decision-making process in implementing Puskesmas management in achieving its activity facilities. According to the Regulation of the Minister of Health of the Republic of Indonesia Number 31 of 2019 article 2, it aims to: 1) Realize the implementation of an integrated Primary Healthcare information system. 2) Ensuring the availability of quality, sustainable, and easily accessible data and information. 3) Improve the quality of health development in its working areas through strengthening the management of Puskesmas. Based on the above background, the researchers are interested in knowing how to implement the Public Health Center Information System at the Baki Sukoharjo Primary Healthcare. This type of research is a descriptive analytic study with a qualitative approach with the aim of getting a picture or description of an actual situation. Primary Healthcare Baki started using SIMPUS Webbased in 2006 which was carried out by medical record personnel, to open the program the Puskesmas had to enter the specified website and then enter an id and password, this program was used to manage patient data and was integrated with P-Care. Optimizing the use of the SIMPUS application and planning the development of the SIMPUS according to the needs of the Puskesmas and the standard for reporting the Primary Healthcare information system Keyword: SIP, Primary Healthcare, SIMPUS